A human monoclonal antibody blocking SARS-CoV-2 infection - Chunyan Wang (Nature Portfolio, 2020)
Vaccines and targeted therapeutics for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are currently lacking. Here, the authors report a human monoclonal antibody capable of neutralizing both authentic SARS-CoV and SARS-CoV-2 by targeting a common epitope.